WNT11, a new gene associated with early onset osteoporosis, is required for osteoblastogenesis. Issue 10 (7th December 2021) - Caetano da Silva, Caroline; Edouard, Thomas; Fradin, Melanie; Aubert-Mucca, Marion; Ricquebourg, Manon; Raman, Ratish; Salles, Jean Pierre; Charon, Valérie; Guggenbuhl, Pascal; Muller, Marc; Cohen-Solal, Martine; Collet, Corinne
Abstract: Monogenic early onset osteoporosis (EOOP) is a rare disease defined by low bone mineral density (BMD) that results in increased risk of fracture in children and young adults. Although several causative genes have been identified, some of the EOOP causation remains unresolved. Whole-exome sequencing revealed a de novo heterozygous loss-of-function mutation in Wnt family member 11 ( WNT11 ) (NM_004626.2:c.677_678dup p.Leu227Glyfs * 22) in a 4-year-old boy with low BMD and fractures. We identified two heterozygous WNT11 missense variants (NM_004626.2:c.217G > A p.Ala73Thr) and (NM_004626.2:c.865G > A p.Val289Met) in a 51-year-old woman and in a 61-year-old woman, respectively, both with bone fragility. U2OS cells with heterozygous WNT11 mutation (NM_004626.2:c.690_721delfs * 40) generated by CRISPR-Cas9 showed reduced cell proliferation (30%) and osteoblast differentiation (80%) as compared with wild-type U2OS cells. The expression of genes in the Wnt canonical and non-canonical pathways was inhibited in these mutant cells, but recombinant WNT11 treatment rescued the expression of Wnt pathway target genes. Furthermore, the expression of RSPO2, a WNT11 target involved in bone cell differentiation, and its receptor leucine-rich repeat containing G protein-coupled receptor 5 ( LGR5 ), was decreased in WNT11 mutant cells. Treatment with WNT5A and WNT11 recombinant proteins reversed LGR5 expression, but Wnt family member 3A (WNT3A) recombinant protein treatment had no effect on LGR5 expression in mutant cells. Moreover, treatment with recombinant RSPO2 but not WNT11 or WNT3A activated the canonical pathway in mutant cells. In conclusion, we have identified WNT11 as a new gene responsible for EOOP, with loss-of-function variant inhibiting bone formation via Wnt canonical and non-canonical pathways. WNT11 may activate Wnt signaling by inducing the RSPO2–LGR5 complex via the non-canonical Wnt pathway.